Sensorimotor Gating in Depressed and Euthymic Patients with Bipolar Disorder: Analysis on Prepulse Inhibition of Acoustic Startle Response Stratified by Gender and State - Matsuo, Junko; Ota, Miho; Hidese, Shinsuke; Teraishi, Toshiya; Hori, Hiroaki; Ishida, Ikki; Hiraishi, Moeko; Kunugi, Hiroshi (Frontiers in Psychiatry, 2018)
Background: Prepulse inhibition (PPI) of the acoustic startle reflex is an operational measure of sensorimotor gating. The findings on PPI deficits in bipolar disorder (BD) are inconsistent among studies due to various confounding factors such as gender. This study aimed to assess sensorimotor gating deficits in patients with BD stratified by gender and state (depressed/euthymic), and to explore related clinical variables. Methods: Subjects were 106 non-manic BD patients (26 BD I and 80 BD II; 63 with depression and 43 euthymic) and 232 age-, gender-, and ethnicity-matched (Japanese) healthy controls. Depression severity was assessed using the Hamilton Depression Rating Scale-21. The electromyographic activity of the orbicularis oculi muscle was measured by a computerized startle reflex test unit. Startle magnitude, habituation, and PPI were compared among the 3 clinical groups: depressed BD, euthymic BD, and healthy controls. In a second analysis, patients were divided into 4 groups using the quartile PPI levels of controls of each gender, and a ratio of the low-PPI group (< 1st quartile of controls) was compared. Effects of psychosis and medication status were examined by the Mann–Whitney U test. Clinical correlates such as medication dosage and depression severity with startle measurements were examined by Spearman’s correlation. Results: Male patients with depression, but not euthymic male patients, showed significantly lower PPI at a prepulse of 86 dB and 120 ms LI than did male controls. More than half of the male patients with depression showed low-PPI. In contrast, PPI in female patients did not differ from that in female controls in either the depressed or euthymic state. Female patients with active psychosis showed significantly lower PPI than those without psychosis. Female patients on typical antipsychotics had significantly lower PPI, than those without such medication. PPI showed a significant positive correlation with lamotrigine dosage in male patients and lithium dosage in female patients. Conclusions: These findings suggest that sensorimotor gating is impaired in male BD patients with depression. However, we obtained no evidence for such abnormalities in female BD patients except for those with current psychosis. The observed associations between medication and startle measurements warrant further investigation.